A COMBINED DETERMINISTIC‐PROBABILISTIC METHOD OF ESTIMATING UNDISCOVERED HYDROCARBON RESOURCES. (July 2017) - Quirk, D. G.; Howe, M. J.; Archer, S. G.
Abstract : Play analysis is used to delineate areas containing geologically similar discoveries and prospects. The yet‐to‐find (YTF) recoverable resource for a conventional play can be predicted using deterministic scenarios utilizing the fact that discoveries within a part play (or common risk segment) can be fitted to a lognormal distribution. Assuming the part play works, a YTF scenario can be made with estimates of (i) the number of drillable prospects, (ii) the average prospect risk, (iii) the resource size of an upside discovery (based on the evaluation of a favoured prospect), and (iv) a downside resource from an implied P99 volume (based on historical data or calculation). A range of YTF is then developed using low, median and high case scenarios. The value of the different scenarios can be estimated provided a minimum economic field size for a generic prospect is available plus a pre‐drill net present value for an average economic discovery. Useful reality checks of YTF estimations include the historical discovery rate, the areal density of traps in analogue settings, the historical average discovery size and the total estimated recoverable resource per unit area. YTF from prospect inventories using Monte Carlo simulations tend to focus on mature areas and are biased to outcomes where all pre‐drill models are correct, unless the prospect sizes are adjusted to account for discoveries which are smaller than predicted by seismic interpretation. YTF estimates will change as information about the play evolves, meaning that it is important that the calculations are kept relatively simple and easy to adjust as new well and seismic data becomes available.